The Influence of Asset Management, Solvency, and Liquidity on Financial Performance in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2021-2023 - Yanita Paulina Br Sebayang; Retnawati Siregar; Hasbiana Dalimunthe; Shabrina Tri Asti Nasution (UNIB Press, 2025)
This study aims to determine and analyze the effect of asset management, solvency, and liquidity on financial performance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. The main problem in this study stems from the phenomenon of fluctuations in Return on Assets (ROA) which shows the inconsistency of the financial performance of companies in the sub-sector, so it is necessary to further explore the financial factors that influence it. The approach used in this study is a quantitative approach with an associative research type. The population in the study was 26 companies, with a purposive sampling technique obtained 20 companies as samples, which were multiplied by 3 years of observation period, resulting in 60 observation data. The data used is secondary data in the form of annual financial reports obtained through the official IDX website (www.idx.co.id). Data analysis techniques were carried out through classical assumption tests, multiple linear regression tests, partial tests (t-tests), simultaneous tests (F-tests), and determination coefficient tests using SPSS software version 25. The results of the study showed that partially, asset management, solvency, and liquidity each had a positive and significant effect on financial performance. Simultaneously, the three independent variables also had a positive and significant effect on the company's financial performance. These findings indicate that efficient asset management, a healthy capital structure, and the company's ability to meet short-term obligations are important factors in improving financial performance. Therefore, companies are advised to pay attention to these three aspects in managerial decision making to achieve long-term financial goals.